Effects of amantadine on behavior, respiratory chain enzymes and creatine kinase in an animal model of schizophrenia - Lucena, David De (Journal of Health & Biological Sciences, 2013)
Introduction: Glutamate dysregulation may be involved in the pathophysiology of schizophrenia, and NMDA antagonists seem to be effective in its treatment. We evaluated the efficacy of amantadine (AMA) in preventing ketamine (KET)-induced effects in an animal model of schizophrenia. Methods: Adult Wistar rats received 10 mg/kg AMA for 10 days, followed by 7 days of 25 mg/kg KET ip. Thirty minutes after the last injection, rats were placed in an open-field apparatus for 60 minutes and killed by decapitation afterwards. Amygdala, hippocampus, prefrontal cortex and striatum were isolated and analyzed for creatine kinase (CK) and respiratory chain enzyme activities. Results: KET increased crossings and reduced grooming, which was not prevented by AMA. KET also increased stereotypic movements, which was partially prevented by AMA. As for CK activity, KET increased it in the prefrontal cortex, striatum and amygdala, and AMA prevented it only in prefrontal cortex and striatum. The activity of complex I was not altered by KET, however, AMA+KET increased it in the striatum and amygdala. KET increased the activity of complex II in the striatum as well, whereas AMA+KET increased it in hippocampus, prefrontal cortex, and striatum. KET did not alter complex I-III activity, whereas AMA+KET increased it in hippocampus and amygdala. AMA+KET also increased complex IV activity in hippocampus and striatum, whereas KET had no effect on this activity. Conclusion: AMA did not prevent most of KET-induced alterations. New animal models should be employed in the study of AMA as a potential novel drug for schizophrenia.